Lo scavo a Parma sotto palazzo sanvitale - Marini Calvani, Mirella, (Archaeopress Roman archaeology ;, 2023)
Palazzo Sanvitale is located in Parma on the left bank of a stream, on the edge of the northeastern quadrant of the urban layout. The palace and garden fill two blocks, separated almost entirely by a minor decumanus. Ceramic and clay scraps from an underlying pit date the laying out of the decumanus towards the end of the 3rd century BC. In the south block, residential buildings recall the housing scenarios of the eastern Cispadana. To the east, a mixtilinear building dates to the 4th century AD. In the other block, superimposed on a primitive housing phase, the remains of a bathhouse dating to the second half of the 2nd century AD are outlined. During the Theoderican age, residential buildings, one of which seals the remains of a mill, filled both blocks. This title is accompanied by essays on the materials from the excavations.